2006
DOI: 10.1111/j.1540-8159.2006.00340.x
|View full text |Cite
|
Sign up to set email alerts
|

Syncopal High‐Degree AV Block Treated with Catheter RF Ablation without Pacemaker Implantation

Abstract: A 23-year-old-female patient had undergone a very successful gastric banding surgery to treat obesity. Six months later she began to present recurrent syncope due to very frequent, intermittent high-degree AV block referred to as pacemaker implantation. The electrophysiological study showed impaired AV nodal conduction but the His-Purkinje conduction was preserved. Partial catheter radiofrequency ablation of the cardiac autonomic nervous system guided by spectral endocardial mapping (cardioneuroablation) was p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 11 publications
0
40
0
2
Order By: Relevance
“…In 2006, Pachon et al reported that spectral mapping–guided vagal denervation achieved symptomatic relief in 6 patients with neural mediate syncope during an average follow‐up of 9 months. They updated their research in 43 patients with important cardioinhibition during a HUT in 2011 .…”
Section: Discussionmentioning
confidence: 99%
“…In 2006, Pachon et al reported that spectral mapping–guided vagal denervation achieved symptomatic relief in 6 patients with neural mediate syncope during an average follow‐up of 9 months. They updated their research in 43 patients with important cardioinhibition during a HUT in 2011 .…”
Section: Discussionmentioning
confidence: 99%
“…The long-term results of increased heart rate must be reconstructed in long-term follow-up studies. Pachon et al 10 reported the long-term results of a patient with high-degree AV block who underwent the cardioneuroablation procedure guided by spectral endocardial mapping. The electrophysiologic parameters normalized and the patient was asymptomatic, leading a normal life at follow-up 21 months later.…”
Section: Discussionmentioning
confidence: 99%
“…Pachon et al 16 reported that the cardiac autonomic modulation through catheter ablation guided by Fast-Fourier Transform analysis was an alternative treatment for refractory neurally mediated syncope. In this study, 6 patients who underwent this procedure had symptomatic relief at a follow-up period up to 9 months.…”
Section: Previous Studiesmentioning
confidence: 99%